PERAN PEKERJA SOSIAL MASYARAKAT (PSM) DALAM PENYELENGGARAAN USAHA KESEJAHTERAAN SOSIAL DI KELURAHAN PASTEUR KECAMATAN SUKAJADI KOTA BANDUNG - anisa antania; Admiral Nelson Aritonang; Milly Mildawati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Abstract Role is a dynamis aspect of position or status by carrying out duties, functions, rights, and obligations according to their job and responsibilities according to their place or position. This research aims to find out the role of the Community Social Worker (PSM) which has been carried out in-depth which includes: 1) initiator, 2) motivator, 3) dynamicator, 4) administrator. The method used in this study is a qualitative descriptive methode approach. The techniques in this study used in-depth interview, observation, and documentation. The criteria for research informants were 2 Community Social Worker, 1 sub-district employee as a Puskesos operator, 1 Sukajadi TKSK, and 2 Social Welfare Service Providers (PPKS). The data sources used are primary data sources and secondary data sources. The results of the study show that the role of Community Social Workers (PSM) is in the dynamic aspect where PSM has not yet held an activity to address social welfare problems due to a lack of coordination with regional coordination and lack of financial support, PSM only collaborates with other parties who hold activities. In the administrator aspect, PSM has not done its job correctly because in recording and reporting PSM only reports via WhatsApp and does not make special records. PSM is also not aware that they will hold regular meetings between PSM’s. based on the results of this research, the researcher proposes a program namely “Increasing the Capacity of Community Social Workers” which aims to improve the quality of PSM’s role capabilities and performance in overcoming social problems in social welfare efforts including in the role of dynamics and administrator roles. Keywords: Role; Community Social Worker; Social Welfare Business.